2021
DOI: 10.3389/fcvm.2021.750016
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Global Longitudinal Strain Is Associated With Myocardial Fibrosis and Predicts Outcomes in Aortic Stenosis

Abstract: Aims: Left ventricular ejection fraction is the conventional measure used to guide heart failure management, regardless of underlying etiology. Left ventricular global longitudinal strain (LV-GLS) by speckle tracking echocardiography (STE) is a more sensitive measure of intrinsic myocardial function. We aim to establish LV-GLS as a marker of replacement myocardial fibrosis on cardiovascular magnetic resonance (CMR) and validate the prognostic value of LV-GLS thresholds associated with fibrosis.Methods and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…27,28 As a consequence, they also have worse cardiac function and advanced hypertrophy, including elevated circulating biomarkers of myocardial wall stress and cardiac injury, which concurred and extended previous studies. 4,[29][30][31] Although nonischemic myocardial fibrosis has been reported in patients with hypertension, 30,32,33 the prognostic significance is not well understood. We observed that most CMR measures of nonischemic myocardial fibrosis (native T1, nonischemic LGE, ECV, and indexed interstitial volume) demonstrated prognostic associations in univariable analyses.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 As a consequence, they also have worse cardiac function and advanced hypertrophy, including elevated circulating biomarkers of myocardial wall stress and cardiac injury, which concurred and extended previous studies. 4,[29][30][31] Although nonischemic myocardial fibrosis has been reported in patients with hypertension, 30,32,33 the prognostic significance is not well understood. We observed that most CMR measures of nonischemic myocardial fibrosis (native T1, nonischemic LGE, ECV, and indexed interstitial volume) demonstrated prognostic associations in univariable analyses.…”
Section: Discussionmentioning
confidence: 99%
“…GLS specifically evaluates longitudinal fiber function, which is more sensitive to ischemia since coronary perfusion extends from the subendocardium and outwards [36][37][38]. Finally, GLS has been shown to correlate closely with the neurohumoral response, infarct size, and myocardial fibrosis [39][40][41]. The primary impediment that has prevented GLS from earlier widespread clinical implementation has been its vendor dependency [42,43].…”
Section: Gls As a Marker Of Ventricular Arrhythmiamentioning
confidence: 99%
“…Myocardial fibrosis is, in general, one of the hallmarks of a failing heart [4]. Among subjects with severe AS, myocardial fibrosis initially develops as a response to pressure overload, exhibiting an interstitial and reversible nature.…”
Section: Introductionmentioning
confidence: 99%
“…Among subjects with severe AS, myocardial fibrosis initially develops as a response to pressure overload, exhibiting an interstitial and reversible nature. However, with the persistence of hemodynamic stress, it becomes an irreversible and substitutive process [4][5][6]. In fact, it is 2 of 14 well known that AS does not only affect the aortic valve but also impacts the myocardium, thereby elevating the risk of heart failure [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation